Association of polymorphism rs1053005 in STAT3 with chronic hepatitis B virus infection in Han Chinese population - Li, Man (BMC Med Genet, 2018)
BACKGROUND: Signal transducer and activator of transcription 3 (STAT3) is involved in hepatitis B virus (HBV) infection and HBV-related hepatocellular carcinoma (HCC). The association between polymorphism rs1053005 and haplotypes formed by rs1053004 and rs1053005 in the 3′UTR of STAT3 and chronic HBV infection has yet to be investigated. METHODS: This study included 567 patients with chronic HBV infection (239 chronic hepatitis, 141 liver cirrhosis and 187 HCC), 98 HBV infection resolvers, and 169 healthy controls. STAT3 rs1053004 and rs1053005 polymorphisms were genotyped by TaqMan SNP Genotyping Assays. RESULTS: The rs1053004 genotype CC [P value by Bonferroni correction (P(c)) = 0.002] and allele C (P(c) = 0.019) were more frequent in patients with chronic HBV infection than in healthy controls. The rs1053005 genotype GG was also more frequent in patients with chronic HBV infection than in healthy controls (P(c) = 0.046). The rs1053004-rs1053005 haplotype T-G was less frequent in patients with chronic HBV infection than in healthy controls (P(c) < 0.001). Haplotype C-A was more frequent in patients with liver cirrhosis than in patients with HCC (P(c) = 0.042). The rs1053004 genotype TC, rs1053005 genotype AG and rs1053004-rs1053005 haplotype T-A were associated with higher HBV DNA levels. CONCLUSIONS: STAT3 rs1053004 and rs1053005 polymorphisms and haplotypes formed by rs1053004 and rs1053005 are associated with chronic HBV infection and the haplotypes appear to be also associated with the development of liver disease. Studies in large sample sizes of patients and control populations are required to verify and extend these findings. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12881-018-0569-x) contains supplementary material, which is available to authorized users.